(3JaSjQ ZQjH GdUMjMjfs - (3eMeO Hf CHj fUQGdMejOj, CHh YHO Gddgs
(3ChdgG (B:s
(3bGd GdTjN GdGeGe GdMGaX GHhYHOGddg GdMejOi QVi Gddg Yfg GdMeO ddg GdPi GfYe YdjfG hSde JSdjeG hHYO aGfG deG aQZfG HYhf Gddg s
(3BNQgG (B:s
(3hai MOjK Ge GdOQOGA bGd OYHS dadGf eXgQ GdYjH Ydjg hPcQ GdbdH HGdcHjQ Jai GdMVhQ BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3dZg JjehQ (B85) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs